Ultrastructural features of astroglial endosomal system state in sepsis-associated encephalopathy - T. V. Shuliatnikova; V. O. Shavrin (Zaporozhye State Medical University, 2020)
Sepsis-associated encephalopathy (SAE) is a common complication of sepsis, with a range of dysfunctional brain disorders. Astrocytes, as the main homeostatic brain cells, play a key role during adaptation of brain tissue to acute damage. The aim. To determine the ultrastructural state of endosomal system of astrocytes in the rat brain under experimental conditions of systemic inflammation. Materials and methods. Male Wistar rats were divided into 2 groups: control group (5 sham-operated animals); the main group with cecal ligation and puncture (CLP, 10 animals). The study of cortex and subcortical white matter of sensorimotor zone in the period between 12 and 24 h after operation was carried out using TEM. Results. In CLP group, starting from 12 h after operation the number of multivesicular bodies (MVBs) increased in astroglial pericaryons and processes. Thus, deceased animals showed a tendency to increase in number of endosomes compared with control and the predominance of their localization in the pericarions of astrocytes. Astroglia of survived animals of CLP group showed the lesser degree of intracellular edema and accumulation of MVBs into perivascular astroglial endfeet, where they exceeded control up to 3 times. Conclusion. In conditions of SAE, starting from 12 h after operation, brain astrocytes show obvious reactive changes with an activation of their endosomal-exosomal machinery, which reflects a high degree of adaptive activity of astroglia and compensatory phase of the pathological state of tissue. One of the ultrastructural signs of this phenomenon is the increased density of MVBs and redistribution of latter predominantly in capillary astrocytic endfeet. The accumulation of MVBs in astrocytic processes may indicate the activation of their intercellular and gliovascular interactions through endo- and exocytosis in the acute phase of adaptive processes under conditions of SAE. This fact emphasizes the special role of astroglia in the compensation of impaired brain homeostasis in SAE.